2010
DOI: 10.1530/rep-10-0068
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite concentrations in follicular fluid may explain differences in fertility between heifers and lactating cows

Abstract: There has been a marked decline in the fertility of dairy cows over the past decades, and metabolomic analysis offers a potential to investigate the underlying causes. Metabolite composition of the follicular fluid, which presents the intrafollicular environment, may be an important factor affecting oocyte maturation and subsequent early embryo development. The aim of the present study was to investigate the metabolic differences between follicular fluid from the dominant follicle of lactating cows and heifers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 45 publications
9
108
2
6
Order By: Relevance
“…Lipid analysis of follicular fluid revealed that ω-6 and ω-3 fatty acid families are the most abundant polyunsaturated fatty acids (PUFAs) in the follicle [6]. These findings strengthen the hypothesis that dietary supplementation of ω-6 and/or ω-3-fatty acids has an important role in oocyte quality and development [7].…”
Section: Introductionsupporting
confidence: 58%
“…Lipid analysis of follicular fluid revealed that ω-6 and ω-3 fatty acid families are the most abundant polyunsaturated fatty acids (PUFAs) in the follicle [6]. These findings strengthen the hypothesis that dietary supplementation of ω-6 and/or ω-3-fatty acids has an important role in oocyte quality and development [7].…”
Section: Introductionsupporting
confidence: 58%
“…By day 44 post-partum, follicular fluid NEFA levels have increased to match that in serum, yet follicular fluid is selectively enriched with palmitic, oleic and linoleic fatty acids (Leroy et al 2005a). These studies highlight that serum NEFA levels are dynamic, increasing dramatically at parturition; and that during lactation follicular fluid NEFA also increase but display a distinct fatty acid profile compared with serum (Leroy et al 2005a, Bender et al 2010. Oocytes of repeat breeder dairy cows were also shown to contain significantly more lipid than oocytes from virgin heifers, even though the COCs isolated from both types of animals were classified as normal good quality (Awasthi et al 2010).…”
Section: Lactation In Dairy Cowsmentioning
confidence: 93%
“…The follicular fluid of both heifers and lactating cows was shown to contain primarily linoleic, oleic, stearic and palmitic acids: however, compared with heifers, the cows had higher levels of at least 24 different fatty acids in follicular fluid, particularly palmitic acid and stearic acid and lower levels of docosahexaeonic acid (Bender et al 2010). In dairy cows, circulating triglyceride levels decrease at parturition, while NEFA levels increase dramatically, relative changes that are also reflected in the follicular fluid (Leroy et al 2004b).…”
Section: Lactation In Dairy Cowsmentioning
confidence: 99%
“…In addition, Bender et al (2010) suggested that the metabolites present in the follicular fluid might be used as markers of oocyte maturation ability as well as of the subsequent embryo development. They investigated the metabolomic profile of follicular fluid obtained from the dominant follicle of lactating cows and heifers using gas chromatography mass spectrometry.…”
Section: Non-invasive Methods For Quality Assessment Of Oocytes/embryosmentioning
confidence: 99%